Tea consumption and risk of stroke in Chinese adults: a prospective cohort study of 0.5 million men and women. Issue 1 (11th November 2019) - Tian, Tian; Lv, Jun; Jin, Guangfu; Yu, Canqing; Guo, Yu; Bian, Zheng; Yang, Ling; Chen, Yiping; Shen, Hongbing; Chen, Zhengming; Hu, Zhibin; Li, Liming; et al.
ABSTRACT: Background: Many cohort studies have explored the relation between tea consumption and stroke risk; however, the conclusions have been inconsistent. In addition, evidence is lacking in China, where the patterns of tea consumption and main types of tea consumed differ substantially from those in high-income countries. Objective: We aimed to systematically assess the association of tea consumption with the risk of stroke based on a Chinese large-scale cohort study. Methods: A total of 487, 377 participants from the China Kadoorie Biobank were included in the present study. Detailed information about tea consumption (including frequency, duration, amount, and tea type) was self-reported at baseline. After ∼4.3 million person-years of follow-up, 38, 727 incident cases of stroke were recorded, mainly through linkage with mortality and morbidity registries and based on the national health insurance system. Results: Overall, 128, 280 adults (26.3%) reported drinking tea almost daily (41.4% men, 15.9% women), predominantly green tea (86.7%). Tea consumption had an inverse and dose–response relation with the risk of stroke ( P trend  < 0.001). Compared with nonconsumers, those who consumed tea occasionally, weekly, and daily had adjusted HRs and 95% CIs of 0.96 (0.94, 0.99), 0.94 (0.90, 0.98), and 0.92 (0.89, 0.95) respectively, with little difference by stroke type. Among those who consumed tea daily, the HRs for stroke decreased with the increasing duration and amount of tea consumed (all P  < 0.001). These inverse associations were significant for green tea but not for other types of tea. Among men, but not women, the inverse relations could be detected, and similar inverse associations could be found for male noncurrent alcohol-consumers and noncurrent smokers as well. Conclusions: Among Chinese adults, higher consumption of tea, especially green tea, was associated with a lower risk of ischemic and hemorrhagic stroke.